The Impact of Entrepreneurial Leadership on MSME Performance With Innovation Process and Innovation Performance as Intervening Variable in MSME Assisted by the Lamongan Regency Cooperative Office - Sarikullah, Intan; Kistyanto, Anang; Nugrohoseno, Dwiarko (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2023)
The purpose of this study was to test and analyze the effect of EL on MSME performance with the innovation process and innovation performance as intervening variables. This research is causality research with a quantitative approach study involving 52 MSME owners who were assisted by the Lamongan Regency Cooperative Office. The sampling technique used incidental sampling with a total of 42 respondents. The statistical analysis used in this research is SEM PLS with the help of SmartPLS 4.0 software. The result of the analysis obtained from this study indicates that EL has a positive and significant effect on MSME performance. EL has a negative and non-significant effect on the innovation process. EL has a positive and significant effect on innovation performance. The innovation process has a positive and non-significant effect on MSME performance. Innovation performance has a positive and significant effect on MSME performance. The innovation process in this study has not been able to mediate the effect of EL and MSME performance.   Innovation performance in this study has been able to mediate the effect of EL and MSME performance.  The research implies that Lamongan Regency Cooperative Service should focus on improving the innovation process aspect to better support the performance of MSMEs.